Speculation in the Agricultural Commodity Market - Czech, Katarzyna (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2013)
This paper studies the role of speculators in explaining agricultural commodity price movements. The spikes in global agricultural commodity prices in 2007-2008 and 2010‑2011 have opened a debate on the contribution of speculation to recent food price volatility. Most academic literature does not support the idea that speculators drive commodity prices beyond fundamental levels. There are, however, some researchers who do find empirical evidence supporting the idea that the activity of speculators affects commodity prices. This paper concludes that the activity of speculators may temporarily overprice or underprice commodity values. It is assumed, however, that both fundamental and financial factors influence commodity prices. Nevertheless, it is difficult to indicate the extent to which each factor separately affects prices.